The effect of using self-regulated learning strategies on the achievement of middle school students in mathematics and their formal thinking (Journal of Imam Al-Kadhim College, 2023)
The research aimed to identify research is to find the effect of self-regulated learning strategies on achievement and formal thinking among female middle school students in mathematics. To achieve the research objectives, the researcher used the quasi-experimental method appropriate to the nature of the research. The research sample consisted of (63) female students from the fourth year of middle school in high school ( Umm Amara for Girls) affiliated with the third Baghdad / Al-Karkh Directorate for the academic year (2022-2023). The sample was chosen intentionally. Section (A) was chosen by (32) to represent the experimental group and Section (B) (31) female students to represent the control group after the two groups were rewarded on the variables (chronological age, previous knowledge, intelligence), I also prepared an achievement test consisting of (24) items and a formal thinking test consisting of (20) items. Their validity and reliability were confirmed, after applying the two tests to the two research groups and using appropriate statistical treatments. The results showed that there was a statistically significant difference at the significance level (0.05) between the average scores of the experimental group who studied according to self-regulated learning strategies and the average scores of the control group who studied according to the usual method of the achievement test and the formal thinking test, in favor of the experimental group؛ A number of recommendations and proposals were presented for the purpose of conducting subsequent research and studies.
Keywords: Keywords: (self-regulated learning strategies, formal thinking, achievement)